Preliminary Assessment of the Potential Embryotoxic Effects of Alstonia boonei De Wild (Apocynaceae) Stem Bark Extract during Organogenesis in Pregnant Sprague-Dawley Rats - Ambe, Daniel Akpe-efiak; Udoh, Etimbuk Iboro; Udoh, Anwanabasi Effiong (African Journal of Clinical Medicine and Pharmacy Research, 2025)
Alstonia boonei stem bark is widely employed in traditional medicine during pregnancy for obstetric purposes, including labour induction, prevention of postpartum haemorrhage, and expulsion of retained placenta. However, the safety of its use during gestation remains scientifically unverified. This study aimed to evaluate the embryotoxic and teratogenic potential of methanolic stem bark extract of A. boonei in pregnant Sprague-Dawley rats. Oral doses of 100, 200, or 400 mg/kg of the extract were administered to pregnant rats (n = 5 per group) from gestational day (GD) 8 to 15, while the control group received no treatment. On GD 16, the animals were euthanized for the assessment of teratogenic indicators, including fetal, placental, and uterine parameters. No statistically significant differences (p > 0.05) were observed in fetal weight, crown–rump length, anogenital distance, or placental and uterine metrics across all groups. However, a significant increase (p < 0.05) in fetal head circumference was recorded at the 400 mg/kg dose (3.49 ± 0.05 mm) compared to the control group (3.32 ± 0.03 mm), indicating possible disruption in central nervous system development. No fetal deaths, malformations, or resorptions were observed. These findings suggest that A. boonei extract is non-teratogenic and embryotoxically safe at doses up to 200 mg/kg, but higher doses may pose risks of dose-dependent developmental alterations. Further investigations are necessary to clarify the mechanisms involved and establish a definitive safety threshold for its use during pregnancy.